Association of the dietary inflammation index with frailty in middle-aged and older adults: a systematic review and meta-analysis - Zhu, Shu-min; Chang, Ping; Wang, Zhen; Yang, Bei; Ye, Hong-fang (Frontiers in Nutrition, 2025)
BackgroundLow-grade of chronic inflammation is a signature of the aging and physiologic frailty may be related to a dysfunctional homeostasis between pro- and anti-inflammatory systems mediated by diverse determinants, including dietary constituents that produce a wide range of biologically active substances, which are important modulators of inflammation in the organism. The Dietary Inflammation Index (DII), a quantitative measure of diet-associated inflammation, has been widely used in studies of a variety of chronic inflammation-related diseases, but the correlation between the DII and frailty has not been uniformly determined.MethodWe searched multiple databases, including CNKI, Wanfang, VIP, Chinese Biomedical Literature Database, PubMed, Embase, Scopus, and Web of Science, to identify studies in English and Chinese examining the association between the dietary inflammatory index and frailty risk. Literature was searched from the time of database construction to January 2025. Two standardized scales were employed for quality assessment: NOS for longitudinal studies and AHRQ tools for cross-sectional research. Sensitivity analyses and publication bias tests were performed using Stata 15.0, and meta-analyses were performed using RevMan 5.3 to calculate the combined odds ratio (OR) and its 95% confidence interval (CI) to assess the DII in correlation with pre-frailty and frailty.ResultsThe meta-analysis examined 15 studies involving a total of 42,130 study participants. The combined results showed that individuals were at increased risk of both frailty [OR = 1.47, 95%CI (1.28, 1.69), p < 0.001] and pre-frailty [OR = 1.54, 95%CI (1.34, 1.76), p < 0.001] in the highest DII category compared to the lowest DII category. Subgroup analyses revealed that DII was significantly and positively associated with the increased risk of frailty in all subgroups of different study geographic areas, types, sample sizes, and dietary assessment tools, whereas the difference between frailty occurrence assessed using the FI debilitation index and DII was not statistically significant in the subgroups of different debilitation assessment tools.ConclusionsAvailable evidence suggests that high pro-inflammatory diets may be associated with an increased risk of frailty, and that dietary strategies that lower the DII could play a role in reducing frailty incidence among older and middle-aged groups.